Book review: Dwaipayan Banerjee. 2020. Enduring Cancer: Life, Death, and Diagnosis in Delhi. (June 2021) - Smith, Robert D.
Dwaipayan Banerjee. 2020. Enduring Cancer: Life, Death, and Diagnosis in Delhi . Durham and London: Duke University Press. x + 224 pp. Notes, bibliography, index. $25.95 (eBook).